Seismic potential of faults in the Granada basin (Betic Cordillera, Spain) - PELAEZ MONTILLA, J. A.; SANZ DE GALDEANO, C.; LLPEZ CASADO, C. (Bulletin of the Geological Society of Greece, 2001)
A fault database has been created for the Granada basin (S Spain) concerning seismic potential in this area. The fault lines have been entered as well as their geometry and displacement rate, when known from accumulated displacement. Empirical relationships have been used between the length or surface of the faults and the maximum magnitude that they can generate. No palaeoseismic recurrence intervals are known, nor palaeoseismic estimates for displacements during earthquakes.